Revisiting the democratic implications of political discussion disagreement: With whom one disagrees matters. Issue 3 (2nd July 2020) - Cao, Xiaoxia
ABSTRACT: An online survey was conducted to explore the political consequences of Facebook political discussion disagreement. It found that within-party disagreement was positively associated with awareness of rationales for oppositional views, political tolerance, and lateness of voting decision but was negatively related to political participation (indicated by voting behavior and Facebook political participation). Between-party disagreement, however, was negatively associated with lateness of voting decision but positively related to political participation. The divergent relationships of discussion disagreement with lateness of voting decision and voting behavior were explained by ambivalent political views. These findings shed light on the democratic implications of discussion disagreement.